PERKEMBANGAN PENDIDIKAN ISLAM DI AWAL KALIMANTAN - Muh. Yusuf; Bahaking Rama; Andi Achruh (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Islam entered Kalimantan in the 5th century AD by peaceful means brought by preachers from Java. Sunan Bonang and Sunan Giri have students in Kalimantan, Sulawesi and Maluku. Sunan Giri's composition is called Kalam Muyang, while Sunan Bonang's composition is called Sumur Serumbung. According to Helius Syamsuddin in his book Islam and Resistance in South and Center Kalimantan in The Nineteenth and Early Twentieth Centuries. Explains that Islam entered South Kalimantan from Java in the 16th century, when the Sultan of Demak helped Prince Banjar, Prince Samudera, to face Prince Temenggung in the battle for the royal throne, in return, Prince Samudra agreed to embrace Islam. In several sources that the authors obtained, the Islamic education efforts pursued by Syekh Muhammad Arsyad Al-Banjari can be classified into three, namely the Cadre of Ulama, Community Teaching and the Establishment of Madrasas. 3. Sheikh Muhammad Arsyad Al-Banjari is a pioneer of teaching Islamic law in South Kalimantan. He had studied Islamic religious sciences in Mecca. Upon returning to his hometown, the first thing he did was to open a place of recitation (a kind of Islamic boarding school) called Dalam Pagar. Islam is spread in almost all areas of West Kalimantan, not only in the coastal areas but also in the interior areas of West Kalimantan. Basically, in West Kalimantan, the majority of the population is Malay, who are synonymous with Islam and generally live on the coasts of rivers or beaches, making Islam easy to be accepted by the community and spreading widely to inland areas. The factors are as follows, through marriage, trade, through preaching, through power and through the arts